Beta-endorphin: replacement of tyrosine in position 27 by tryptophan increases analgesic potency--preparation and properties of the 2-nitrophenylsulfenyl derivative. - Li, C H (1982)
An analog of human beta-endorphin with tryptophan in position 27 has been synthetized by the solid-phase method. Bioassay of the analog showed that it had almost 4 times the analgesic potency of the parent hormone but only 68% of the opiate receptor-binding activity. The peptide is the most potent analgesic among the known synthetic analogs of beta-endorphin. The 2-nitrophenylsulfenyl derivative of the analog has been prepared and shown to have a lower analgesic potency and a higher opiate receptor-binding activity than the parent compound.